Sustainable rural development: What is the role of the agri-food sector? - Martin Petrick; Gertrud Buchenrieder (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2007)
This volume of proceedings, available both as hard copy and pdf, is an edited compilation of selected contributions to the IAMO Forum 2007, which will be held in Halle (Saale), Germany, at the Leibniz Institute of Agricultural Development in Central and Eastern Europe from 27 to 29 June 2007. CONTENTS: Rural-urban interlinkages and regional development; Flemming Just. Sustainability assessment of rural development: A review of methodologies; Adinyira Emmanuel, Oteng-Seifah Samuel, Adjei-Kumi Theophilus. Post-soviet transition, rural development and the peasant problem: The cultural and institutional economic dimension; Ernst-August Nuppenau. Economic impacts of land market development: Evidence from Moldova; Dragos Cimpoies. Regional specificity of rural labour allocation and migration in Ukraine; Oleksandr V. Zhemoyda. Infrastructure as a determinant of rural non-farm employment: The case of Ukraine; Mariya Portyanko. Informal loans - Alternatives or supplements to bank credit for Polish farms; Alina Danilowska. Development of innovative technologies in rural finance; Anna Bondarenko, Roman Kosodiy, Eugeniy Mishenin. Efficiency of index-based crop insurance in Russian agriculture; Raushan Bokusheva, Marina Sannikova, Olaf Heidelbach. Rural credit partnerships and their role in the development of agriculture in Kazakhstan; Sholpan Gaisina. Taking the hands off the rural credit market: An evidence from China; Xiangping Jia, Franz Heidhues, Manfred Zeller. Rural development policy and food industry development: Investigations of small firms in Denmark; Derek Baker, Jens Abildtrup, Anders Hedetoft. Dairy food chain restructuring in Poland - Causes and impacts; Dominika Milczarek, Agata Malak-Rawlikowska, Jan Falkowski. Strategies to face the socio-economic crisis in a rural territory: The case of the Baronnies Provençales (Drôme, Southeast France); Ana Poletto, Richard Raymond, Emilien Barussaud. Empirical assessment of Fuzzy Intervention-Logics: The case of rural development in East Germany; Anne Margarian. Comprehensive rural development in China: Strategy and implementation challenges; Achim Fock, Karin Fock. Who is benefiting from rural development policies? Andrea Pufahl, Regina Grajewski, Barbara Fährmann. Anticipated impacts of GMO introduction on farm profitability in Poland; Mariusz Maciejczak, Adam Was
urn:nbn:de:gbv:3:2-5477
Keywords: 330